PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA POINTER BY TELKOM INDONESIA - Dita Fitriana Julliasari; Bonifasius MH. Nainggolan; Verry Cyasmoro (LPPM Universitas Asa Indonesia, 2018)
Purpose- This study aims to determine the compensation, motivation, work discipline affect partially and simultaneously on pointer’s performance at Telkom Indonesia. Design/methology/approach- The population in this study were pointers at Telkom Indonesia with samples used in this study as many as 100 people. The sampling technique used is saturated sampling. Data analysis method used in this research is validity test, relicompensation test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test and linearity test). While hypothesis testing includes F test, t test and partial correlation analysis and coefficient of determination (r²). Findings- From the analysis results can be seen that Compencation (X1), Motivation (X2), and Work Rotation (X3) has an influence on both partial and simultaneous pointers performance